The Cohesion of the Prologue on the Hunger Games Trilogy: A Discourse Analysis - Ann Mellene Capuy Fernandico (JETAL: Journal of English Teaching & Applied Linguistic, 2020)
Cohesion is designed to deal with words and phrases that generate a pattern of relations between lexical elements and structures to build an integral and logical text. The analysis of cohesion aims to connect central concepts to the context of writing intended to pursue standards of communication, writing styles, textuality, and a practice of discourse. Accordingly, this study analyzes the cohesion found in the Hunger Games Trilogy by Suzanne Collins. The method of this research is a discourse analysis focusing on Systematic Functional Linguistics (SFL) developed by M.A.K. Halliday. Based on the analysis, the prologue of The Hunger Games and Catching Fire novels can be described in the terms of field, tenor, and mode creating the contextual parameter. The text of the novels is written and is clearly detached, explicit, planned and integrated. While links were observed as characters and places were repeatedly written. The conclusion can be drawn that the two novels aim to tell a story. Furthermore, the texts do not instruct the reader on what to do but rather, it tells what the characters of the story did, are doing, or will do. The novels also implore the reader to read further beyond the prologue and to the main story.